Palliative Radiation Therapy for Macroscopic Hematuria Caused by Urothelial Cancer - Haiqin Zhang; Hidehiro Hojo; Vijay Parshuram Raturi; Naoki Nakamura; Masaki Nakamura; Masayuki Okumura; Yasuhiro Hirano; Atsushi Motegi; Shun-Ichiro Kageyama; Sadamoto Zenda; Tetsuo Akimoto (Palliative Medicine Reports, 2020)
Background: To assess the efficacy and toxicity profiles of palliative radiation therapy (RT) for macroscopic hematuria (MH) caused by urothelial cancer. Methods: A total of 25 urothelial cancer patients with MH who underwent palliative RT between 2008 and 2018 were analyzed in this retrospective study. The hematuria-free survival (HFS) time was defined as the period from complete resolution of MH to the recurrence of MH, death, or the last follow-up examination. Adverse events were classified according to the Common Terminology Criteria for Adverse Events version 4.0. Results: By the end of the median follow-up duration of 90 days (11?886 days), complete resolution of MH had been achieved in 22 patients (88%), and the median interval between the start of RT and resolution of MH was 9 days (2?179 days). Of the 22 patients in whom the symptom resolved, 9 (41%) developed recurrent MH, and the median time to relapse of MH was 129 days (30?692 days). The median RT dose was 30 Gy (20?40 Gy). Nine (36%) patients received a blood transfusion before the RT. The three-month HFS rate was 52.1%. There was a significant difference in the three-month HFS rate between patients with and without a history of pretreatment blood transfusion (HFS rate: 34.6% vs. 61.5%, p?=?0.03). Grade 2 urinary tract pain and grade 3 diarrhea were seen in one patient each. Conclusion: Palliative RT appeared to be effective with limited toxicities for urothelial cancer patients with MH.